Expression Of Vimentin in Oral Squamous Cell Carcinoma - يوسف , باسمة (Latakia University Journal -Medical Sciences Series, 2021)
Almost 90% all Oral and Oropharyngeal Cancers are Squamous Cell Carcinoma,the most malignant tumor of Epithelial Origin. The aim of this Study is to determine the Expression of Vimentin in tumor Tissues of Oral Squamous Cell carcinoma and the relationship between the Expression of Vimentin and tumor Grad. Material and Methods: Archived paraffin-embedded formalin fixed specimens from (28) Patients with oral squamous cell carcinoma were collected in Dental Faculty during (2013-2019). And all of them were histologicaly monitored to confirm the diagnosis in histology and pathology Department .then the blocks were sectioned with microtome and prepared for immunostainer for detection Vimentin. Results: there was a significant statistical associated between Vimentin and Tumor Grad (p<0,05). And vimentin can be used as predictor for tumor Prognosis.